La construcción mediática de la realidad: el caso Prestige - Ferreira, Miguel; Gómez-monedero, María José; Guillén, Rosario; Márquez, Antonio; Ongil, Marta; Zappia, Gustavo; Sanjorge, Amalia; Guillén, Ángel (Nómadas. Critical Journal of Social and Juridical Sciences, 2006)
Sin resumen